The diversity and plasticity of descending motor pathways rewired after stroke and trauma in rodents - Inoue, Takahiro; Ueno, Masaki (Frontiers in Neural Circuits, 2025)
Descending neural pathways to the spinal cord plays vital roles in motor control. They are often damaged by brain injuries such as stroke and trauma, which lead to severe motor impairments. Due to the limited capacity for regeneration of neural circuits in the adult central nervous system, currently no essential treatments are available for complete recovery. Notably, accumulating evidence shows that residual circuits of the descending pathways are dynamically reorganized after injury and contribute to motor recovery. Furthermore, recent technological advances in cell-type classification and manipulation have highlighted the structural and functional diversity of these pathways. Here, we focus on three major descending pathways, namely, the corticospinal tract from the cerebral cortex, the rubrospinal tract from the red nucleus, and the reticulospinal tract from the reticular formation, and summarize the current knowledge of their structures and functions, especially in rodent models (mice and rats). We then review and discuss the process and patterns of reorganization induced in these pathways following injury, which compensate for lost connections for recovery. Understanding the basic structural and functional properties of each descending pathway and the principles of the induction and outcome of the rewired circuits will provide therapeutic insights to enhance interactive rewiring of the multiple descending pathways for motor recovery.